THE IMPLEMENTATION OF MOBILE PASPOR (M-PASPOR) POLICY IN PASSPORT APPLICATION AT IMMIGRATION OFFICE CLASS I SPECIAL TPI MEDAN - Rania Harahap; Februati Trimurni (Indonesian Journal of Social Sciences, Policy and Politics, 2023)
M-Paspor was launched with the aim of making passport services more transparent, accountable, and fast. However, there are still problems with the implementation, namely that the application often has errors, the quota is limited, and there are still many people who do not know the M-Paspor application. Therefore, this study aims to describe the implementation of the M-Paspor Policy in passport applications at TPI's Medan Special Class I Immigration Office. The research method used in this study is qualitative with a descriptive approach. The results of the study indicate that the implementation of the M-Paspor Application Policy in passport applications at the Immigration Office Class I Khusus TPI Medan has been running in accordance with the specified objectives. In the organizational element, the available resources are sufficient, but since the COVID-19 pandemic, the budget can only be used by 60%, and the passport printer needs to be repaired or replaced so that passport issuance is not hampered. In addition, the organizational structure and methods are quite clear and simple.